2021
DOI: 10.3390/polym13030404
|View full text |Cite
|
Sign up to set email alerts
|

Melt- vs. Non-Melt Blending of Complexly Processable Ultra-High Molecular Weight Polyethylene/Cellulose Nanofiber Bionanocomposite

Abstract: The major hurdle in melt-processing of ultra-high molecular weight polyethylene (UHMWPE) nanocomposite lies on the high melt viscosity of the UHMWPE, which may contribute to poor dispersion and distribution of the nanofiller. In this study, UHMWPE/cellulose nanofiber (UHMWPE/CNF) bionanocomposites were prepared by two different blending methods: (i) melt blending at 150 °C in a triple screw kneading extruder, and (ii) non-melt blending by ethanol mixing at room temperature. Results showed that melt-processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 84 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…In an effort to quantitatively analyze the role of the elastic modulus on cellular activity, the upregulation in the osteochondral functionalities is plotted against the elastic modulus (values in the log scale) in Figure . For benchmarking purposes, the elastic modulus for an identical grade of UHMWPE (267 ± 22.4 MPa) is taken from the literature . It is clear that the osteochondral induction and maturation can be modulated by tailoring the elastic modulus in the newly developed PVDF-TPU-BT-based hybrid composite, in a manner quantitatively better than commercial UHMWPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to quantitatively analyze the role of the elastic modulus on cellular activity, the upregulation in the osteochondral functionalities is plotted against the elastic modulus (values in the log scale) in Figure . For benchmarking purposes, the elastic modulus for an identical grade of UHMWPE (267 ± 22.4 MPa) is taken from the literature . It is clear that the osteochondral induction and maturation can be modulated by tailoring the elastic modulus in the newly developed PVDF-TPU-BT-based hybrid composite, in a manner quantitatively better than commercial UHMWPE.…”
Section: Discussionmentioning
confidence: 99%
“…For benchmarking purposes, the elastic modulus for an identical grade of UHMWPE (267 ± 22.4 MPa) is taken from the literature. 35 It is clear that the osteochondral induction and maturation can be modulated by tailoring the elastic modulus in the newly developed PVDF-TPU-BT-based hybrid composite, in a manner quantitatively better than commercial UHMWPE. Any specific trend (linear) could not be established with the limited data points.…”
Section: Discussionmentioning
confidence: 99%
“…This is because CNF materials are lighter in weight with a high surface area to volume ratio and higher strength and stiffness as compared to other micro-size fibers. It has been reported that CNF acts as a nucleating agent in a polymer matrix which improves the crystallinity and mechanical properties of the material [41][42][43]. Besides that, a small amount of CNF (1 wt.%-3 wt.%) is usually enough to significantly improve the mechanical performance of polymer composites.…”
Section: Mechanical Performancementioning
confidence: 99%
“…However, this material has a relatively low Young's modulus which limits its applications. Sharip et al [42] had found that with the inclusion of 0.5% CNF in UHMWPE, the mechanical properties of the composite were improved as compared to neat UHMWPE. It was also found that the yield strength, elongation at break, Young's modulus and toughness of CNF/UHMWPE were higher by 28%, 61%, 47% and 45%, respectively, as compared to the neat UHMWPE.…”
Section: Medicalmentioning
confidence: 99%
“…[25] Compared with pure UHMWPE, the ratcheting strain rate of the composites is reduced by more than 24%, and a new viscoplastic constitutive model is proposed to describe the uniaxial ratcheting behavior. The properties of the composites mainly depend on their chemical composition and the morphological structure of the polymer on the microscale and heterogeneous system, [26][27][28][29] and the difference in the mechanical properties of UHMWPE and its composites before and after aging is also due to the difference in the microstructure caused by the thermal oxidation degradation of the polymer at low temperature. Many studies have been performed on the mechanical properties and creep properties of UHMWPE containing CNF.…”
Section: Introductionmentioning
confidence: 99%